Internal quality of laying hens’ commercial eggs according to storage time, temperature and packaging - Lis Lorena Melúcio Guedes; Camilla Mariane Menezes Souza; Ana Paula de Oliveira Saccomani; Daniel Emygdio de Faria Filho; Diana Suckeveris; Douglas Emygdio de Faria (Acta Scientiarum. Animal Sciences, 2016)
Current assay evaluates the internal quality of eggs of Hy-Line W-36 hens, according to storage time, temperature and packaging. Two equal experiments, starting one day apart, were conducted with 140 eggs each. The two experiments were divided into two phases, from 1 to 9 days and from 9 to 21 days, in a randomized block design. In the 1st phase, the treatments were arranged in a factorial 2 x 3+1, packaging (with or without), time (3, 6 and 9 days), with control on the 1st day. In the 2nd phase, treatments were arranged in a factorial design 2 x 2 + 1, packaging (with or without), cooling (with or without), and control on the 9th day. Egg weight, albumen, yolk and shell percentage, yolk index and Haugh unit were evaluated. The internal quality was reduced (p < 0.05) during storage and the internal quality of eggs kept at room temperature decreased (p < 0.05), whereas eggs stored under refrigeration showed the same quality (p > 0.05) on the 9th and 21st days. Packaging assured better quality (p < 0.05), but not similar to the quality of refrigerated eggs. Results showed that the internal quality of the eggs was worse when there was no refrigeration during storage time and that packages provided better internal quality, although not as effective as cooling.